'Getting a battering': The perceived impact of demand and capacity imbalance within the Police Service of England and Wales: A qualitative review. (June 2016) - Elliott-Davies, M; Donnelly, J; Boag-Munroe, F; Van Mechelen, D
Since 2010, the number of officers in the Police Service of England and Wales (PSEW) has fallen by 12% (Home Office, 2015). Although there has been much public debate over the impact of these reductions (Barrett, 2014; Blanchard, 2014; May, 2015; Shaw, 2015; White, 2015), such arguments have mostly lacked robust supporting evidence. This study aims to help inform future debate by providing qualitative evidence via semi-structured focus groups with serving police officers. Semi-inductive thematic analysis revealed a dynamic set of elements, perceived by officers as both affecting and being affected by the PSEW's demand and capacity balance.